United Nations Commission on International Trade Law (UNCITRAL) Yearbook 2016 - United Nations (United Nations, 2020)
This Yearbook is a compilation of all substantive documents related to the work of the Commission and its Working Groups. It also reproduces the annual Report of the Commission which is published as Supplement No. 17 of the